How can future methodologies be applied in the planning process? Case study of the bus park and railway station in Kisumu, Kenya and Centralen Gothenburg, Sweden - Nikulina, Varvara (My University, 2015)
Sustainability is one of the key words of our modern society. Is it the case in every country? To what extent is it integrated in the present state situation and the planning process? Until recently, transportation has never been on the priority list for reaching developmental goals of the United Nations. Continuously increasing demand for transportation services worldwide is one of the main present-day urban challenges. A thought-through integrated transportation system can ensure confidence and comfort for the passengers. On the contrary, the lack of such a system or a poorly managed system prevents the economy from realizing its potential. Looking at the cases of the bus park and railway station in Kisumu, Kenya and Centralen Gothenburg, Sweden, the question of usefulness of future methodologies in the planning process is investigated. The thesis analyzes backcasting, foresighting and SymbioCity approaches and their applicability to the compared given conditions of Kisumu and Gothenburg. Field work preparation, different field study methodologies, analytical methods and comparative analyses of the future methodologies in the planning process are used to reach the conclusion. First, the planning processes in Kisumu and Gothenburg are analyzed. In order to assess the usefulness of the future methodologies in the planning process, the systems of the stations in Kisumu and the current state in both cities are examined. The main conclusion is that backcasting is identified as suitable for both cases. It is easy to apply (can be used by an individual) and avoids “lock-in” solutions. Moreover, it begins with creation of the common desired vision and is useful when traditional approaches do not work. The other two methodologies (foresighting and SymbioCity approach) would be beneficial if certain conditions are met.
Keywords: Annan samhällsvetenskap; Other Social Sciences